Is one or two infusions better in the first week of low-dose ketamine treatment for medication-resistant depression? A post hoc pooled analysis of randomized placebo-controlled and open-label trials. (December 2021) - Chen, Mu-Hong; Wu, Hui-Ju; Li, Cheng-Ta; Lin, Wei-Chen; Tsai, Shih-Jen; Hong, Chen-Jee; Tu, Pei-Chi; Bai, Ya-Mei; Mao, Wei-Chung; Su, Tung-Ping
Abstract: Background: Whether a second ketamine infusion in the first week improves the antidepressant, antisuicidal, and anti-inflammatory effects of the first low-dose ketamine infusion remains unclear. Methods: A total of 78 patients with medication-resistant depression were allocated to receive two ketamine infusions (n = 30; days 1 and 4), a single ketamine infusion (n = 24; only day 1), or normal saline placebo infusion (n = 24; only day 1). The Montgomery-Asberg Depression Scale (MADRS) and 17-item Hamilton Rating Scale for Depression (HDRS) were administered before and at 40 min, 240 min, day 2, day 4, day 5, and day 7 after infusion. Serum concentrations of interleukin (IL)-2 and tumor necrosis factor (TNF)-α were assessed. Results: Two ketamine infusions improved the overall depressive symptoms (p < 0.001) and melancholic symptoms (p < 0.001) than a single ketamine or placebo infusion. The antisuicidal effect did not differ between the ketamine treatment groups. Two ketamine infusions increased TNF-α levels compared with a single ketamine or placebo infusion (p = 0.015). A single ketamine infusion improved the TNF-α-to-IL-2 ratio, an index of average anti-inflammatory effect, than two ketamine infusions or a single placebo infusion (p = 0.027). Discussion: Repeated low-dose ketamine infusions improved the antidepressant effect, but not the antisuicidal effect, compared with a single infusion. However, repeated ketamine infusions may exert a lesser anti-inflammatory effect than a single infusion.